An assessment of resource availability for problem based learning in a Ghanaian University setting. Issue 2 (3rd April 2017) - Okyere, Gabriel Asare; Tawiah, Richard; Lamptey, Richard Bruce; Oduro, William; Thompson, Michael
Abstract : Purpose: The purpose of this paper is to assess the differences pertaining to the resources presently accessible for problem-based learning (PBL) among six colleges of Kwame Nkrumah University of Science and Technology (KNUST) in Ghana. Design/methodology/approach: Data for the study are the cross-sectional type drawn from 1, 020 students. Poisson and zero-inflated Poisson (ZIP) models were implemented on the data to ascertain the variations regarding the extent of resources available for PBL across the colleges of the university. Findings: The study outlines the specific resources accessible for PBL across college levels of KNUST. On aggregate, 25.7 per cent reported that their respective colleges have sufficient resources, while 74.3 per cent indicated otherwise. The ZIP model exhibited superiority over the Poisson model, when compared under a Vuong test. As per the ZIP model, none of the colleges appeared to differ significantly in terms of having sufficient resource for PBL. Practical implications: Findings are applicable to informed decision-making which targets achieving quality education through the use of PBL. Access to sufficient resources that meet the needs of colleges or departments of a University is emphasized. Originality/value: The application of Poisson and ZIP models to aggregated count data in a PBL setting is novel.